Aerosol number concentrations and new particle formation events over a polluted megacity during the COVID-19 lockdown. (15th August 2021) - Yadav, Shailendra Kumar; Kompalli, Sobhan Kumar; Gurjar, Bhola Ram; Mishra, Rajeev Kumar
Abstract: The present study investigates the particle number concentrations and size distributions in the ultrafine and fine-sized regimes over a polluted megacity, New Delhi (28.75° N, 77.12° E), India. The experiments were conducted during the periods (April–May 2020) of strict social and travel restrictions (lockdown) imposed by the Government of India aiming to contain the spread of Coronavirus Disease 19 (COVID-19) pandemic. The different phases of the COVID-19 lockdown witnessed restrictions of varying magnitudes with the significant cessation of anthropogenic sources, viz., industrial, road, railways, and air traffic emissions. Using this unique opportunity, the impact of varying urban emissions on particle number size distributions and new particle formation events were examined. The mean total number concentrations were in the range of ~ (2–3.5) x 10 4  cm −3 and depicted a gradual increase (~26%) with progressive unlock of the anthropogenic activities. At the same time, accumulation particle concentrations were doubled. However, ultrafine particles (UFP) (diameter < 100 nm) dominated (50–88%) the total number concentrations during most of the days and several new particle formation (NPF) events resulting in elevated (2–5 fold) UFP concentrations were observed. Subsequently, the particles grew to larger sizes with rates ~3.31–8.37 nm h −1 . The NPF events occurred during the daytime, and during the events, a clear enhancement in the concentrations of [H2 SO4 ] proxy (2–3.5 × 10 7 molecules cm −3 ; 2–3 orders higher than the non-event values) suggesting the role of strong gas-phase photochemistry. Also, some of the NPF events were associated with increased odd oxygen concentrations [Ox  = O3 +NO2 ], indicating the regional nature of the precursors and participation of VOC precursors in nucleation/growth. Interestingly, different classes of NPF events were seen during the strictest lockdown period, whereas more frequent and well-defined NPF events were witnessed when anthropogenic activities were opened up with conditional relaxations. These events demonstrated the competition between source strengths of precursor vapors from anthropogenic activities and primary particles acting as condensation sink restricting NPF. This study highlighted that urban pollution mitigation policies need to consider ultrafine particles emanating from the secondary aerosol formation process from traffic emissions. Graphical abstract: Temporal variation of particle number size distribution (PNSD) during the study. The arrows on the bottom indicate the new particle formation events. Image 1 Highlights: The impact of the COVID-19 lockdown on fine and ultrafine particle concentrations is examined over the megacity, New Delhi. Several new particle formation (NPF) events during the lockdown period were noticed. NPF events highlighted the balance between precursor vapor sources and condensation sink. Notable contribution from traffic emissions to UFP bursts with progressive relaxation of lockdown.